PENGARUH MODEL PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI DI SEKOLAH DASAR - Syatriana Syatriana; Siti Halidjah; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
Abstract The process of learning writing skills should use the media. Media is used to help learners develop their ideas and thoughts. Based on these statements, we used a learning model that the teacher had never used before. Learning model in question is the picture and picture model. This study uses quasi experimental with Nonequivalent Control Group Design. The research sample consisted of class III A as control group and class III B as experiment group selected by purposive sampling technique. The data collection tool in the form of multiple choice test for pretest and posstest using essay 1 question is used to collect data. Influence of picture and picture model on writing skill description in SD Negeri Pontianak city. The result of this research is t tested t_hitung (4,83) and t_ (table) (α = 5% and dk = 21 + 20 - 2 = 39) 2,0198. Because t_count (4.83)> t_tabel (2.0189), H0 is rejected and Ha accepted. Picture and picture model give influence to the skill of writing description essay at Pontianak City Elementary School.  Keywords: Picture and Picture, Writing Skills, Authors Description